#TITLE_ALTERNATIVE# - ALFATH FAHLEVI (NIM : 10211074), REZA
Sophisticated monitoring systems and be able to perform difficult missions increasingly needed. One of the systems used for monitoring is the Unmanned Aerial Vehicle (UAV). One type of UAV is Quadcopter. Quadcopter is an aircraft type which is driven by four motors with a propeller. Airfoil shape of the blades creates lifting force and torque that is opposite to the direction of rotation of the propeller. Because there are four propellers that work, then the movement quadcopter based on the RPM of each motor. Torque incurred need be arranged so that all the torque that emerge from each of the motor in order to eliminate mutual quadcopter can reach a stable state. Failsafe system designed intended to minimize the possibility of system failure at quadcopter. The failsafe designed give a good result which will make quadcopter land automatically when a system failure is detected such as loss of signal from the transmitter or when the battery has reached the minimum threshold. By adding cameras and the stabilizer system, then we can do the monitoring on an area, especially areas that are difficult to reach or have a high risk. Camera stabilizer control system that is designed use digital control system equipped with IMU sensor to determine the position of the quadcopter. Due to the IMU sensor used is very sensitive to vibrations and changes of the angle, the camera stabilizer system needs to be given the tolerance value of changes the angle so that the servo does not always move when changes occur only fairly small angle. Camera stabilizer system designed give a better result when we give the tolerance value to the servo movement about 2 degrees to change the angle that occurs. It can be seen from the reconstruction image data of pixel matrix difference of two successive images that obtained 5 to 10 times better result than the image without the tolerance value.